2019
DOI: 10.1111/jocn.14873
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' information practice in municipal health care—A web‐like landscape

Abstract: Aim To uncover the characteristics of nurses' information practice in municipal health care and to address how, when and why various pieces of information are produced, shared and managed. Background Nursing documentation in the electronic patient record has repeatedly been found unsatisfactory. Little is known about how the information practice of nurses in municipal health care actually is borne out. In order to understand why nursing documentation continues to fail at living up to the expected requirements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
(57 reference statements)
1
24
0
4
Order By: Relevance
“…The individual information needs of healthcare workers differ with experience, formal health education and familiarity with a given patient (Bing-Jonsson et al, 2016;Østensen et al, 2019). It is therefore difficult to decide what level of detail to put into a care plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual information needs of healthcare workers differ with experience, formal health education and familiarity with a given patient (Bing-Jonsson et al, 2016;Østensen et al, 2019). It is therefore difficult to decide what level of detail to put into a care plan.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that recording in EPRs is viewed as a less urgent task, that healthcare workers experience competing interests and that the EPR system does not support their workflow (Vabo, Slettebø, & Fossum, 2016). The EPR system is just one of multiple information sources used in long-term care and does not always support nursing practice due to availability at point of care (Østensen, Bragstad, Hardiker, & Hellesø, 2019). These are all factors that can influence the quality of nursing records and their ability to facilitate the continuity of care.…”
Section: Nurse Recordkeepingmentioning
confidence: 99%
“…Working longer at the current workplace is likely to reflect a certain degree of continuity of care in itself. Homecare nurses with more years of experience may perceive information as more available as they know their patients well and have memorized much information, so that searching for information in the electronic documentation system may seem redundant [14]. It may also indicate the skill of more experienced homecare nurses to locate patient information in the municipality's documentation system.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive qualitative research has explored information practices within different municipal health care settings and has revealed a general lack of comprehensive nursing documentation [14][15][16][17][18]. This suggests that health care personnel has to make decisions based on incomplete information [18], which can lead to an incorrect allocation of services or even malpractice, with potentially serious consequences for care recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite sound arguments for applying a more flexible approach to home nursing care, relying solely on nurses’ experiences and knowledge about the patient can also have adverse consequences. Østensen et al (2019) found that nurses who worked full time in long-term care facilities often knew their patients well and, therefore, considered reading electronic patient records to be redundant. By extension, knowing the patient can become an implicit and obvious knowledge that may be overlooked, in terms of documentation in the patient record, which can result in some observations being regarded as “private” information, and patient care may risk becoming person-dependent.…”
Section: Discussionmentioning
confidence: 99%